Representasi Strategi Public Relations dalam Film Our Brand Is Crisis - Chisler, Zevanya; Paramita, Sinta (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This research aims to study the components of how Public Relations (PR) strategies are represented in the film Our Brand is Crisis using Roland Barthes' semiotic theory. This study explores the representation of PR strategies through visual, verbal and symbolic elements that create meaning in political communication. With a qualitative approach, this study found four main Public Relations (PR) strategies: publication, persuasion, argumentation, and image formation. All of these strategies are used to build public perceptions of candidates, influence people's opinions, shape political identities, and create successful leadership myths. These strategies are used to build public perceptions of candidates, influence opinions, shape political identities, and create leadership myths. Through Roland Barthes' semiotics analyzing denotation, connotation, and myth, this study illustrates how political narratives create effective candidate images. The results of this research encourage further research on the role of semiotics in the study of political communication and provide insight into the importance of strategic communication in building images in the context of mass media and politics. Penelitian ini bertujuan untuk mempelajari komponen mengenai bagaimana strategi Public Relations (PR) di representasikan dalam film Our Brand is Crisis menggunakan teori semiotika Roland Barthes. Studi ini mengeksplorasi representasi strategi PR melalui elemen visual, verbal, dan simbolik yang menciptakan makna dalam komunikasi politik. Dengan pendekatan kualitatif, Studi ini menemukan empat strategi Public Relations (PR) utama: publikasi, persuasi, argumentasi, dan pembentukan citra. Semua strategi ini digunakan untuk membangun persepsi publik terhadap kandidat, mempengaruhi pendapat orang, membentuk identitas politik, dan menciptakan mitos kepemimpinan yang berhasil.Strategi-strategi ini digunakan untuk membangun persepsi publik terhadap kandidat, memengaruhi opini, membentuk identitas politik, dan menciptakan mitos kepemimpinan. Melalui semiotika Roland Barthes menganalisis denotasi, konotasi, dan mitos, studi ini menggambarkan bagaimana narasi politik menciptakan citra kandidat yang efektif. Hasil penelitian ini mendorong penelitian lebih lanjut tentang peran semiotika dalam studi komunikasi politik dan memberikan wawasan tentang pentingnya komunikasi strategis dalam membangun citra dalam konteks media massa dan politik.